Effect of lithographically-induced strain relaxation on the magnetic domain configuration in microfabricated epitaxially grown Fe81Ga19 - Beardsley, R.P.; Parkes, D.E.; Zemen, J.; Bowe, S.; Edmonds, K.W.; Reardon, C.; Maccherozzi, F.; Isakov, I.; Warburton, P.A.; Campion, R.P.; Gallagher, B.L.; Cavill, S.A.; et al. (Nature Publishing Group, 2017)
We investigate the role of lithographically-induced strain relaxation in a micron-scaled device fabricated from epitaxial thin films of the magnetostrictive alloy Fe81Ga19. The strain relaxation due to lithographic patterning induces a magnetic anisotropy that competes with the magnetocrystalline and shape induced anisotropy to play a crucial role in stabilising a flux-closing domain pattern. We use magnetic imaging, micromagnetic calculations and linear elastic modelling to investigate a region close to the edges of an etched structure. This highly-strained edge region has a significant influence on the magnetic domain configuration due to an induced magnetic anisotropy resulting from the inverse magnetostriction effect. We investigate the competition between the strain-induced and shape-induced anisotropy energies, and the resultant stable domain configurations, as the width of the bar is reduced to the nanoscale range. Understanding this behaviour will be important when designing hybrid magneto-electric spintronic devices based on highly magnetostrictive materials.